Realizing Professional Human Resources Through Implementing Orientation at Al Azhaar Islamic Elementary School Tulungagung - Darmawan, Dendys; Maunah, Binti (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
The implementation of Human Resources (HR) orientation in Islamic education institutions has a considerable role in realizing professional human resources, which in turn has a major impact on the progress and development of institutions. This study aims to provide an overview of the implementation of new HR orientation activities in superior Islamic educational institutions. This study uses a descriptive qualitative research method. This research was conducted at Al Azhaar Tulungagung Islamic Elementary School. The results of this study indicate: (1) orientation activities for new HR to create professional HR in the form of internships for 3 (three) months, (2) orientation activities at Al Azhaar can provide mental-psychological and technical readiness for new HR, both educators and education staff, (3) orientation activities at Al Azhaar can be said to be effective because they are based on the right understanding, goals, principles, steps, and materials to create professional human resources. Islamic educational institutions should institutionalize structured, internship-based orientation programs for new personnel as a mandatory component of talent management, complemented by clear performance indicators and post-orientation follow-up mechanisms to ensure sustained staff professionalism and overall institutional performance.